Formation of self-regulation culture of physical education faculty - S.F. Kudin (Physical Education of Students, 2016)
Purpose: to experimentally substantiate effectiveness of pedagogic conditions of self-regulation culture formation of future physical culture teachers. Material: in the research 110 3rd year students of physical education faculty participated. The students were questioned. The level of students’ anxiety was assessed. Results: Implementation of the author’s course in educational process facilitated formation of students’ self-regulation skills and abilities; raises confidence and self estimation; influences positively on functional state. It was found that students acquire ability to consciously observe their own verbal constructs of negative thinking and create positive alternatives. Conclusions: preparing of future physical culture teachers stipulates his (her) ability to effectively fulfill professional functioning in the aspect of health preservation. The necessary conditions of self-regulation culture formation are formation of students’ holistic value-meaningful attitude to individual health and health of surrounding people.